2022
DOI: 10.3390/agriculture12091500
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High Temperature on Germination, Seedling Growth and Enzymatic Activity of Wheat

Abstract: Global warming has increased the temperature significantly over a large extent both spatially and temporally. The threat of heat stress during the germination and seedling establishment stages in the wheat crop is now more prevalent than ever before. The present experiment assessed the effect of elevated temperature on the germination and early seedling growth of wheat genotypes. The seeds were sown under four temperatures, viz., 20 °C, 25 °C, 30 °C and 35 °C; the germination, seedling vigor and enzyme activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Seed germination and early seedling growth are the most sensitive stages for plant stand establishment under extreme environmental stresses [ 31 ]. Increased temperature stress has been found to have a strong negative effect on seed germination potential resulting in poor germination [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Seed germination and early seedling growth are the most sensitive stages for plant stand establishment under extreme environmental stresses [ 31 ]. Increased temperature stress has been found to have a strong negative effect on seed germination potential resulting in poor germination [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Te positive response to germination of preheating chickpea seed might be due to its role in infuencing the permeability of the membranes which ultimately leads to the activation of enzymes involved in protein synthesis and carbohydrate metabolism [26]. Sharma et al [27] revealed that enzymes such as superoxide dismutase (SOD) are activated at optimal temperatures, around 20 °C and this increases seed germination. Improved germination of chickpea seed due to halopriming can be attributed to the ability of KNO 3 to break dormancy in seeds of many species [28].…”
Section: Discussionmentioning
confidence: 99%
“…From seed germination to seed setting, all stages are sensitive at various degrees. An elevated temperature of 30-35 • C has been shown to significantly reduce the germination rate of most wheat genotypes [24]. Temperatures above 33 • C will cause a yield reduction in rice [25] and affect the seed viability and germination potential during the vegetative stages [26], because heat stress affects three main factors of germination: soil moistures, enzyme activities, and production of hormones.…”
Section: Negative Effects Of Abiotic Stressesmentioning
confidence: 99%